Export of Dissolved Organic Carbon from a Ponded Freshwater Marsh Receiving Diverted Mississippi River Water - R. D. DeLaune; C. B. Johnson; R. P. Gambrell; A. Jugsujinda (The Scientific World Journal)
A series of diversion projects has been implemented to reintroduce Mississippi River water into Louisiana's coastal wetlands in order to reduce wetland loss. The export of dissolved organic carbon (DOC) was measured in a 3,700-ha ponded freshwater marsh that receives diverted Mississippi River water. Results show that highly organic marsh soil and plant material are a source of DOC. DOC, on average, was 3 mg/l greater in outlet water as compared to the concentration in river water entering the wetland. DOC in water leaving the marsh was higher in summer months, with a concentration up to 18 mg/l. Based on a discharge of 1,000 ft3/sec (28.3 m3/sec), it was estimated that the equivalent of 7,335 kg/day of DOC would be exported from the marsh into Lake Cataouatche, located in the northern portion of the Louisiana Barataria Basin estuary. Results suggest that river diversion would likely increase the export of DOC from the marsh as compared to normal transport associated with rainfall and tidal exchange.